2006
DOI: 10.1007/s00542-006-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, experiment of a microactuator using magnetic fluid for micropump application

Abstract: This paper presents the characteristics of the first microactuator using magnetic fluid (MF). MF actuators with flat and corrugated diaphragms are fabricated by the micromachining technique and their deflections are measured. The MF actuator consists of an inductor, a fluid chamber filled with magnetic fluid, and a parylene diaphragm. In the presence of the magnetic field, magnetic fluid easily deforms its shape and generates some pressure. The relation between the MF pressure and magnetic flux density is obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…14 Set-up configuration of a ferrofluid gyroscope with sensing coils axis perpendicular to the ferrofluid drop axis, given by And ò et al The ability to manipulate ferrouids into a variety of geometries makes them attractive as components in actuators. Sim et al 186 reported a device where a ferrouid is enclosed within a corrugated Parylene diaphragm and can be controlled by a DC magnetic eld to produce bending of the diaphragm, generating a pressure of 2.8 kPa that is suitable for micro pump applications. This actuator can be used to control an optically active surface of a microlens.…”
Section: Ferrofluidic Actuators and Transducersmentioning
confidence: 99%
“…14 Set-up configuration of a ferrofluid gyroscope with sensing coils axis perpendicular to the ferrofluid drop axis, given by And ò et al The ability to manipulate ferrouids into a variety of geometries makes them attractive as components in actuators. Sim et al 186 reported a device where a ferrouid is enclosed within a corrugated Parylene diaphragm and can be controlled by a DC magnetic eld to produce bending of the diaphragm, generating a pressure of 2.8 kPa that is suitable for micro pump applications. This actuator can be used to control an optically active surface of a microlens.…”
Section: Ferrofluidic Actuators and Transducersmentioning
confidence: 99%
“…Fluids of this type are generally a suspension of magnetic particles in a carrier medium. Sim et al (2006) used the response of a magnetic fluid to a field to actuate a parylene diaphragm in a micropump. The salient features of this pump are that at a field of 110 Gauss, the diaphragm could be deflected by more than 200 μm to provide a pressure of 2.8 kPa.…”
Section: Electromagnetic and Magneticmentioning
confidence: 99%
“…The mechanical device is provided with moving parts that displace fluid when actuated [115]. As an alternative, many non-mechanical pumps always recur to several unique physical and chemical effects in the microscale to realize the kinetic energy impartation [116][117][118][119][120]. Compared with the electroosmotic pump and the electrolytically actuated bubble micropump as mentioned in the above section, researchers also harnessed their creativity to develop a device that converts the internal energy of the micro/ nanofluid to mechanical energy to exert force.…”
Section: Internal To Mechanicalmentioning
confidence: 99%